(3GdeLGdS GdSHYI GdJi hbYJ Hjf GdhRjQ hHjf eWQGf EjdjGs - (3GdeWQGf EjdjGs
(3ChdgG (B:s
(3MeOkG def Ndb GdEfSGf HCMSf Jbhje CeG HYO dbO CMGW Ydei HQSGdI JYdhG bOQkG hJSehG aNQkG Ydi cJH GdeJbOejf hGdeJCNQjf ef GdfUGQi ddeWQGf EjdjG CjgG GdeNdU ai CeGfJg GdHGPd WdHkG dBNQJg s
(3BNQgG (B:s
(3hYfO hbhYg YdjgG hJCedg eVehfgG cJH NWg ai BNQgG HeG gPg McGjJg bQCJgG hCLGH Yf GdcJGH GdUGOQ Edjg ef eYfGgG HeG fSNJg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI SYjO GdOjhg Li (B- (3GdYQGb s
Keywords: (3GdOjGfGJ GdCNQis